1994
DOI: 10.1093/nar/22.16.3280
|View full text |Cite
|
Sign up to set email alerts
|

Identification of catalytically relevant amino acids of the extracellularSerratia marcescensendonuclease by alignment-guided mutagenesis

Abstract: By sequence alignment of the extracellular Serratia marcescens nuclease with three related nucleases we have identified seven charged amino acid residues which are conserved in all four sequences. Six of these residues together with four other partially conserved His or Asp residues were changed to alanine by site-directed PCR-mediated mutagenesis using a variant of the nuclease gene in which the coding sequence of the signal peptide was replaced by the coding sequence for an N-terminal affinity tag [Met(His)6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 32 publications
(26 reference statements)
2
64
0
Order By: Relevance
“…Both the CJE0566 and CJE1441 protein sequences contained a conserved domain of the NUC superfamily (SMART accession no. SM00477) characteristic for DNA/RNA nonspecific endonucleases (11,12). Moreover, the translated sequences contained a DRGH motif (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the CJE0566 and CJE1441 protein sequences contained a conserved domain of the NUC superfamily (SMART accession no. SM00477) characteristic for DNA/RNA nonspecific endonucleases (11,12). Moreover, the translated sequences contained a DRGH motif (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PDOC00821} in which histidine is the active site residue (11,12). Although the amino acid sequences and the predicted 3D structures of CJE0566 and CJE1441 share similarity with members of this family, the sequences deviate from the DRGH motif in their fifth residue (Q3T).…”
Section: Discussionmentioning
confidence: 99%
“…B., unpublished). In spite of the fact that the primary (Ball et al, 1987), secondary (Friedhoff et al, 1994a), tertiary (Miller et al, 1994) and quaternary structures (Filimonova et al, 1981 ;Friedhoff et al, 199413;Miller and Krause, 1996) of the Serratia nuclease are known, its mechanism of action is not understood. The crystal structure analysis of the Serratia nuclease (Miller et al, 1994), in conjunction with a site-directed mutagenesis study of residues con-served in the Serratia nuclease and related enzymes (Friedhoff et al, 1994a), suggested that His89 [numbering according to the sequence of the mature protein (Ball et al, 19921 and Glu127 among other residues are involved in catalysis; their role, however, is not clear.…”
mentioning
confidence: 99%
“…The extracellular nuclease (NucA) is the major focus of this study. This nuclease has been well characterized biochemically and structurally (15,37), but little is known about its biosynthesis or export. Here we show that the secretion of this nuclease occurs in two steps.…”
mentioning
confidence: 99%